Comparative Analysis of MSMEs to Revamping the Procedures for Availing Finance - Nageswararao, Dr. K. Siva; Latha, Dr. Challa Madhavi; M, Dr.Venkataramanaiah. (The journal of contemporary issues in business and government, 2021)
Micro Small and Medium Enterprises (MSMEs) are the engine of economic growth which constitutes the majority of business enterprises and they are vital for employment generation, income creation and poverty alleviation. MSMEs are the second largest source of employment next only to agriculture.The main objective of this paper is to analyse the financial barriers faced by the MSMEs while attempted to avail the financing opportunities from the financial institutions. The researcher conducted exploratory factor analysis to the proposed variables in the model by using KMO and Bartlett’s test. Simple linear regression analysis has been conducted to compare Micro, Small and Medium enterprises. The researcher proposed type of industry, tenure of business, procedural complications, lack of knowledge about finance schemes, difficulty in documentation are the independent variables of the study which may leads for availing the finance from different financial organizations. Further, the researcher afforded to know the impact of availing finance of MSMEs in Guntur district, Andhra Pradesh, India.